Paleodiet and niche breadth in Middle Miocene rodents and ungulates from northern South America revealed through stable isotope analyses - Laura E. Arias-Concha; Michael J. Ziegler; Patrick Roberts; Francisco J. Urrea-Barreto; Darin Croft; Siobhán B. Cooke; Catalina Zorro; Jana Ilgner; Erin Scott; Andres Vanegas-Vanegas; Cesar Augusto Perdomo; Andrés Link (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Dental topography and diet in marsupials and comparisons with primates - Dorien de Vries; Amy Gao; Darin A. Croft; Garrett Brown; Nicholas Burkart; April Connell; Ellie Gahan; Emily Spinks; Robin M.D. Beck (Journal of Mammalian Evolution, 2026)
Dental topography is a powerful tool for investigating the relationship between diet and tooth shape in mammals. Here, we test whether dental topographic metrics (DTMs) can accurately predict diet in marsupials based on 81 lower molars from 43 extant species in 12 families (six of the seven extant orders), and compare them to DTMs of primates with similar diets. DTMs tested included Dirichlet normal energy (DNE) and variants (ariaDNE, convex DNE, and ariaDNE CV), orientation patch count rotated (OPCR), and Relief Index (RFI). We also investigate the use of the ratio of trigonid to talonid height (TriTaHI) as an additional DTM. Notably, RFI and ariaDNE were less sensitive to sample composition and scanning modality than OPCR and ariaDNE CV were. For marsupials, highest dietary classification accuracy of the leave-one-out quadratic discriminant analysis was achieved by combining ariaDNE, RFI, molar size, and TriTaHI of lower second and third molars, resulting in 69.2% accuracy. In contrast, the primate sample of lower second molars reached highest classification accuracy (80.4%) when using only ariaDNE, RFI, and molar size. When using a clade-based cross-validated approach (i.e., using the primate sample to predict marsupial diets and vice versa), only ariaDNE, RFI, and molar size were needed to obtain the maximum classification accuracy (69.7% when classifying primates using the marsupial training set; and 61.8% vice versa). The comparative dataset of this study should prove useful for studies aiming to reconstruct the diets of fossil mammals that lack phylogenetically close extant analogues.

Pass on the grass? The unexpected “last supper” of hypselodont Pachyrukhinae (Notoungulata, Mammalia) from the late Neogene of northwestern Argentina - Matías Alberto Armella; Darin Andrew Croft (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Convergence, divergence, and novelty in the ungulate-like hindlimbs of South American litopterns - Malena Lorente; Gabriela I. Schmidt; Darin A. Croft (Journal of Mammalian Evolution, 2025)

The flora, fauna, and paleoenvironment of the late Middle Miocene Quebrada Honda Basin, Bolivia (Eastern Cordillera, Central Andes) - Caroline A.E. Strömberg; Beverly Z. Saylor; Russell K. Engelman; Angeline M. Catena; Daniel I. Hembree; Federico Anaya; Darin A. Croft (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Resolution of the long-standing controversy over the type species of the genus Pseudotypotherium (Notoungulata, Typotheria, Mesotheriidae) - Marcos Fernández-Monescillo; Darin A. Croft; François Pujos; Pierre-Olivier Antoine (Palaeoworld, 2023)

A seventh carnivorous metatherian taxon (Sparassodonta) from the late Miocene-early Pliocene Santa María group of Catamarca Province, Argentina - Russell K. Engelman; Darin A. Croft (Journal of South American Earth Sciences, 2023)

How to weigh a fossil mammal? South American notoungulates as a case study for estimating body mass in extinct clades - Allison Nelson; Russell K. Engelman; Darin A. Croft (Journal of Mammalian Evolution, 2023)

A New Glyptodont (Xenarthra: Cingulata) from the Late Miocene of Argentina: New Clues About the Oldest Extra-Patagonian Radiation in Southern South America - Daniel Barasoain; Alfredo E. Zurita; Darin A. Croft; Claudia I. Montalvo; Víctor H. Contreras; Ángel R. Miño-Boilini; Rodrigo L. Tomassini (Journal of Mammalian Evolution, 2022)

Comparative Endocranial Anatomy, Encephalization, and Phylogeny of Notoungulata (Placentalia, Mammalia) - Fernando A. Perini; Thomas E. Macrini; John J. Flynn; Kanvaly Bamba; Xijun Ni; Darin A. Croft; André R. Wyss (Journal of Mammalian Evolution, 2022)

Head of the Class: John R. Wible’s Transformative Insights Into Mammalian Craniodental Anatomy - Guillermo W. Rougier; Timothy J. Gaudin; Darin A. Croft (Journal of Mammalian Evolution, 2021)

New Chinchillid Rodents (Hystricognathi: Caviomorpha) from Northern Chile and Bolivia Fill a 17-Million-Year Gap in the Pan-Chinchilline Fossil Record - Darin A. Croft; John J. Flynn; André R. Wyss; Reynaldo Charrier; Federico Anaya (Journal of Mammalian Evolution, 2021)

Australogale leptognathus, gen. et sp. nov., a Second Species of Small Sparassodont (Mammalia: Metatheria) from the Middle Miocene Locality of Quebrada Honda, Bolivia - Russell K. Engelman; Federico Anaya; Darin A. Croft (Journal of Mammalian Evolution, 2020)

New Remains of Megathericulus patagonicus Ameghino, 1904 (Xenarthra, Tardigrada) from the Serravallian (Middle Miocene) of Bolivia; Chronological and Biogeographical Implications - Diego Brandoni; Alfredo A Carlini; Federico Anaya; Phil Gans; Darin A Croft (Journal of Mammalian Evolution, 2018)

New Middle Miocene Caviomorph Rodents from Quebrada Honda, Bolivia - Darin A. Croft; Jennifer M. H. Chick; Federico Anaya (Journal of Mammalian Evolution, 2011)

The Beginning of the Age of Mammals in South America, Part III - Darin A. Croft (Journal of Mammalian Evolution, 2011)

New Data on Miocene Neotropical Provinciality from Cerdas, Bolivia - Darin Andrew Croft; Federico Anaya; David Auerbach; Carmala Garzione; Bruce J. MacFadden (Journal of Mammalian Evolution, 2009)